2018
DOI: 10.1101/381921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Central Dicer-miR-103/107 Controls Developmental Switch of POMC Progenitors into NPY Neurons and Impacts Glucose Homeostasis

Abstract: 33Proopiomelanocortin ( 43Moreover, in utero silencing of miR-103/107 causes perturbations in glucose homeostasis.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The loss of Efnb1 in POMC neurons is associated with alterations in glucose tolerance and losses of parasympathetic nerve activity and insulin secretion. These findings are consistent with previous studies, which reported that affecting either POMC signaling, circuits or POMC neuron survival leads to impaired glucose homeostasis (1012). Surprisingly, loss of Efnb1 in POMC neurons does not perturb food intake or body weight.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The loss of Efnb1 in POMC neurons is associated with alterations in glucose tolerance and losses of parasympathetic nerve activity and insulin secretion. These findings are consistent with previous studies, which reported that affecting either POMC signaling, circuits or POMC neuron survival leads to impaired glucose homeostasis (1012). Surprisingly, loss of Efnb1 in POMC neurons does not perturb food intake or body weight.…”
Section: Discussionsupporting
confidence: 94%
“…P6, P14, and P22 Pomc -Cre;tdTomato male mice (n=2-3 animals/age), 16-18 week-old Pomc -Cre;tdTomato; Efnb1 loxP/0 , Pomc -Cre;tdTomato, Pomc -Cre;tdTomato; Efnb2 loxP/loxP , and Pomc -Cre;tdTomato; Efnb1 loxP/loxP , Pomc -Cre;tdTomato; Efnb2 loxP/loxP , Pomc -Cre;tdTomato female mice were transcardially perfused with 4% PFA (n=3/group). 20 µm-thick brain and pancreas sections were processed for immunofluorescence using standard procedures (10,52,58). The primary antibodies used for IHC were as follows: rabbit anti-vGLUT2 (1:500, Synaptic Systems), rabbit anti-VAChT (1:500, Synaptic Systems), guinea-pig anti-insulin (1:500, Abcam).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ARH contains neuronal populations that are topographically distributed (Croizier et al, 2010). Of which, POMC‐expressing neurons were mainly observed in the dorsolateral ARH while NPY/AgRP‐coexpressing neurons mostly localized in the ventromedial ARH close to the medial eminence and the third ventricle (Figure 15a,f,g) (Croizier et al, 2018; Lein et al, 2007). By using immunohistochemical approaches, confocal imaging and 3D reconstruction, we observed PHAL‐positive putative terminal boutons surrounding and in contact with POMC‐expressing neurons (Figure 15a–d).…”
Section: Resultsmentioning
confidence: 99%